Holbergordbogen – en nordisk forfatterskabsordbog - Eegholm-Pedersen, Svend (LexicoNordica, 2006)
Holberg-Ordbog (Copenhagen, Oslo 1981–88) covers the complete works of Ludvig Holberg, an outstanding Dano-Norwegian author in the first half of the 18th century, versatile as a dramatic (comedy), historical, and essayistic writer. This paper presents the five volume lexicographic work, its scope and function as an author’s dictionary of the so-called selective thesaurus type. By its editorial practice the Holberg dictionary is a descendant of the Danish national dictionary, Ordbog over det danske Sprog (1919– 56), in return the specialist dictionary can – on many points – furnish important supplementary material for Danish lexicography in general, as is shown by some examples. A final section discusses briefly some other Scandinavian and European author’s dictionaries and concordances/indexes, and the author sides with Wiegand (1986) and Mattausch (1990) in their underlining of the importance of semantic author’s dictionaries versus concordances and indexes.